Dexamethasone-sparing strategies in anthracycline and cyclophosphamide-based chemotherapy with a focus on 5-HT3 receptor antagonists: a network meta-analysis - Watanabe, Daichi; Iihara, Hirotoshi; Kobayashi, Ryo; Fujii, Hironori; Mori, Ryutaro; Kumada, Keisuke; Shimizu, Masahito; Futamura, Manabu; Suzuki, Akio (Frontiers in Oncology, 2024)
The effectiveness of a dexamethasone-sparing strategy in the treatment of breast cancer with anthracycline-cyclophosphamide therapy when combined with firstgeneration 5-HT3 receptor antagonists (RAs) and neurokinin-1 RAs is unclear. This is attributable to a lack of evidence from direct comparison of multiple doses of DEX to a single dose of DEX in combination with first-generation 5-HT3 RAs in anthracyclinecyclophosphamide therapy. Our goal was to clarify the impact of dexamethasonesparing strategies that involve both first-generation 5-HT3 RAs and palonosetron when combined with neurokinin-1 RAs, using a network meta-analysis.A literature search was conducted on PubMed/Medline for articles published up to July 4, 2023. We included randomized controlled trials which assessed the efficacy of antiemetic regimens which combined 5-HT3 RAs and dexamethasone, with or without neurokinin-1 RAs, for the initial dose in anthracycline-cyclophosphamide therapy for patients with breast cancer. The primary outcome was the proportion of patients achieving a complete response during the delayed phase (CR-DP).The difference in the proportion of patients achieving CR-DP between multiple and single doses of dexamethasone was 0.1% (95%CI: -12.4 to 12.5) with palonosetron and neurokinin-1 RAs, compared to 5.3% (95%CI: -13.4 to 23.0) with a single dose of a first-generation 5-HT3 receptor antagonist. Additionally, the difference was 12.7% (95% CI: -2.8 to 28.2) when comparing palonosetron against first-generation 5-HT3 RAs in combination with a single dose of dexamethasone and neurokinin-1 RAs.Palonosetron is recommended rather than a single dose of first-generation 5-HT3 RAs in dexamethasone-sparing strategies for anthracycline-cyclophosphamide therapy.